2022
DOI: 10.1155/2022/5267498
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Detection using Ensemble Learning

Abstract: One of the most challenging tasks for clinicians is detecting symptoms of cardiovascular disease as earlier as possible. Many individuals worldwide die each year from cardiovascular disease. Since heart disease is a major concern, it must be dealt with timely. Multiple variables affecting health, such as excessive blood pressure, elevated cholesterol, an irregular pulse rate, and many more, make it challenging to diagnose cardiac disease. Thus, artificial intelligence can be useful in identifying and treating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The authors suggested that hybrid approach can be used to extend the existing work for better prediction. Alqahtani et al [17] proposed a framework for cardiovascular disease prediction using ensemble learning and deep learning techniques. In the experiment, the random forest algorithm achieved the highest accuracy (88.65%), precision (90.03), recall (88.03), f1-score (88.02), and ROC-AUC value (92).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that hybrid approach can be used to extend the existing work for better prediction. Alqahtani et al [17] proposed a framework for cardiovascular disease prediction using ensemble learning and deep learning techniques. In the experiment, the random forest algorithm achieved the highest accuracy (88.65%), precision (90.03), recall (88.03), f1-score (88.02), and ROC-AUC value (92).…”
Section: Related Workmentioning
confidence: 99%
“…Techniques such as data imputation for handling missing values, detection, and replacement of outliers using the Boxplot method have been used to achieve better results than other related works. Boosting, bagging, stacking, and majority vote Cleveland heart disease dataset (publicly available) 85.48% with majority vote [10] Recursive feature elimination and GB Do 89.78% [12] XGB with Bayesian optimization Do 91.80% [14] CatBoost, GB, XGB, and ADB Do 83.60% with ADB [17] DNN, KDNN, XGB, KNN, decision tree, and random forest Do 88.65% with random forest [18] Naïve Bayes, linear model, logistic regression, decision tree, random forest, SVM, and HRFLM Do 88.40% with HRFLM Our method XGB, ADB, and GB Do 92.20% for BDT…”
Section: Comparative Analysismentioning
confidence: 99%
“…The GWO approach is used to select features, and an SVM model is then used to predict heart disease using the resulting subset of features [2]. Singh and Kumar proposed various machine learning models that can be used for heart disease prediction [3] whereas Javed et al [4] proposed a different approach by using ensemble learning for heart disease prediction. Eid Emaryet al [5] suggested a system to follow when using GWO algorithm integrated in machine learning.…”
Section: Literature Surveymentioning
confidence: 99%
“…In [1] proposed an ensemble model on a dataset consisting of 70000 records with 13 attributes. Random Forest is used for feature selection and Pearson's Coefficient to examine correlation between features.…”
Section: Literature Reviewmentioning
confidence: 99%